2017
DOI: 10.3354/meps12140
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the northernmost spawning habitat of Dosidicus gigas with implications for its northwards range extension

Abstract: The jumbo squid Dosidicus gigas is an ecologically and commercially important species whose northernmost geographic limit is the Gulf of California. However, over the last decades this species has extended its geographic distribution polewards, with associated impacts on the ecosystem. The origin of range-shifting individuals is poorly understood; therefore, we aimed to identify and characterize the northernmost spawning habitat of this species. Implications of the location and oceanographic conditions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…About 98% of the paralarvae collected in the present study were identified as belonging to the SD complex. However, previous studies of SD complex paralarvae off northwest Mexico that used molecular identification confirmed predominance of D. gigas paralarvae in the region north of 18 °N (Fernandez-Alvarez et al , 2018;Gilly et al , 2006;Ramos et al , 2017;Sanchez-Velasco et al , 20 16) . In contrast, south of 18 °N under properly tropical conditions, molecular methods identified S. oualaniensis as the numerically dominant SD complex paralarvae species (Staaf et al , 2013).…”
Section: Laboratory Processingmentioning
confidence: 86%
See 1 more Smart Citation
“…About 98% of the paralarvae collected in the present study were identified as belonging to the SD complex. However, previous studies of SD complex paralarvae off northwest Mexico that used molecular identification confirmed predominance of D. gigas paralarvae in the region north of 18 °N (Fernandez-Alvarez et al , 2018;Gilly et al , 2006;Ramos et al , 2017;Sanchez-Velasco et al , 20 16) . In contrast, south of 18 °N under properly tropical conditions, molecular methods identified S. oualaniensis as the numerically dominant SD complex paralarvae species (Staaf et al , 2013).…”
Section: Laboratory Processingmentioning
confidence: 86%
“…Bibliographic research on SD complex paralarvae presence in the study area was made to compare the GAM output with historical data. Most of the bibliographic data correspond to areas outside the main sampled area, along the Pacific coast of Baja California Peninsula (Camarillo-Coop et al , 2010;Ramos et al, 2017;Palomares-Garcia et al , 2018;Garcia-Guillen et al , 2018;Molina-Arenas, 2018).…”
Section: Seasonal and Interannual Variation Of Potential Nursery Habitatmentioning
confidence: 99%
“…Environmental oscillations can affect the range distribution of marine mobile organisms (Lan, Evans, & Lee, ; Norton, ; Parmesan, ; Ramos et al., ; Stewart, Hazen, Foley, Bograd, & Gilly, ; Zeidberg & Robison, ). Given this fact, we expected spatial variation in the distribution of striped marlin EFL caused by a large‐scale phenomenon as ENSO.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning techniques such as neural networks, random forests, support vector machines and the maximum entropy model have shown promise in improving fishery forecasts [11][12][13]. However, most of the current models use the monthly average value of marine environmental factors in the fishing area [14,15]. These variables cannot reflect the monthly temporal and spatial dynamics and complexity of the marine environment and thus make it difficult to accurately analyze the temporal and spatial dynamic habitat of jumbo flying squid.…”
Section: Introductionmentioning
confidence: 99%